A Comparative Study of the Implementation of Sustainable Forest Management Policies in China and Indonesia: Lessons from Forest Management Practices - Wijaya Halim, Hadi (Faculty of Communication Science | Universitas Pancasila Jakarta, Indonesia, 2025)
Sustainably preserving the functions of forests is the aim of sustainable forest management (SFM), which considers social, economic, and environmental issues. For the sake of present and future generations, the FAO defines SFM as a dynamic concept that